Light affects behavioral despair involving the clock gene Period 1. - Iwona Olejniczak; Jürgen A Ripperger; Federica Sandrelli; Anna Schnell; Anna Schnell; Laureen Mansencal-Strittmatter; Katrin Wendrich; Ka Yi Hui; Andrea Brenna; Naila Ben Fredj; Urs Albrecht (PLoS Genetics)
Light at night has strong effects on physiology and behavior of mammals. It affects mood in humans, which is exploited as light therapy, and has been shown to reset the circadian clock in the suprachiasmatic nuclei (SCN). This resetting is paramount to align physiological and biochemical timing to the environmental light-dark cycle. Here we provide evidence that light at zeitgeber time (ZT) 22 affects mood-related behaviors also in mice by activating the clock gene Period1 (Per1) in the lateral habenula (LHb), a brain region known to modulate mood-related behaviors. We show that complete deletion of Per1 in mice led to depressive-like behavior and loss of the beneficial effects of light on this behavior. In contrast, specific deletion of Per1 in the region of the LHb did not affect mood-related behavior, but suppressed the beneficial effects of light. RNA sequence analysis in the mesolimbic dopaminergic system revealed profound changes of gene expression after a light pulse at ZT22. In the nucleus accumbens (NAc), sensory perception of smell and G-protein coupled receptor signaling were affected the most. Interestingly, most of these genes were not affected in Per1 knock-out animals, indicating that induction of Per1 by light serves as a filter for light-mediated gene expression in the brain. Taken together we show that light affects mood-related behavior in mice at least in part via induction of Per1 in the LHb with consequences on mood-related behavior and signaling mechanisms in the mesolimbic dopaminergic system.